2022
DOI: 10.1093/advances/nmab148
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and Sustainable Dietary Patterns in Children and Adolescents: A Systematic Review

Abstract: The need to adherence to healthy and sustainable dietary pattern in pediatric age is discussed worldwide, being linked to a progressively incidence of non-communicable diseases in adulthood. The aims of this systematic review were to summarize the healthy and/or sustainable dietary patterns, defined a priori, described in the literature for use among the pediatric age; to evaluate the adherence to these dietary patterns and identify the health-related benefits associated with the adherence to these patterns. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 158 publications
1
12
0
2
Order By: Relevance
“…After duplicates were removed, we screened n = 139 abstracts. The research team screened all of the potential full text papers (n = 26), and, finally, a total of n = 11 papers [24][25][26][27][28][29][30][31][32][33][34] met the inclusion criteria, as described in Figure 1. Among a total number of 11 systematic reviews included in the present umbrella review, only 2 papers included a meta-analysis [25,28].…”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed, we screened n = 139 abstracts. The research team screened all of the potential full text papers (n = 26), and, finally, a total of n = 11 papers [24][25][26][27][28][29][30][31][32][33][34] met the inclusion criteria, as described in Figure 1. Among a total number of 11 systematic reviews included in the present umbrella review, only 2 papers included a meta-analysis [25,28].…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review assessed 50 healthy and sustainable dietary patterns in children and adolescents by measuring adherence to healthy and/or sustainable dietary patterns, with the Mediterranean diet as the most studied dietary pattern. The review found that higher adherence to the reviewed sustainable dietary patterns was associated with lower body fat, waist circumference, blood pressure, and metabolic risk, but there was no consensus regarding the association with BMI (Teixeira et al, 2022) and concluded that there is a need for a new sustainable instrument or test in association with, e.g., the ecological and water footprints since no studies provide evidence of the sustainability. Recently, a 30-item Sustainable-Healthy-Diet (SHED) Index score was developed for measuring healthy and sustainable individual diets and reflecting the nutritional, environmental, and sociocultural aspects of sustainable diets (Tepper et al, 2021) that found a significant correlation between the SHED index score and the Mediterranean diet score, confirming the MD as a sustainable diet.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the cumulative data reporting the possible beneficial effects of MD diet on children, this narrative review, showed that few studies have evaluated the effects of MD on specific age groups [ 52 , 53 , 76 ]. As we move towards more “tailored” medicine [ 77 ], it is important to perform ad hoc studies for each age group to avoid biased generalizations.…”
Section: Discussionmentioning
confidence: 99%